Fabrication of graded porous hydroxyapatite by using coconut fibre - Ahmad Kasyfullah Arifin
This study was carried out to develop sample hydorxyapatite (HA) cylindrical with have porous in particular part for example his external layers has solid part while on the inside it exist porous. Further it can make as bone implant for the compact bone part and spongy bone.